Mineralogical and morphological properties of individual dust particles in ice cores from the Tibetan Plateau - Wu, Guangjian; Zhang, Xuelei; Zhang, Chenglong; Xu, Tianli (Journal of Glaciology, 2016)
Using a field emission scanning electron microscope and energy-dispersive X-ray spectrometer (FESEM-EDS), individual insoluble dust particles in ice cores recovered from the northern (Dunde), western (Murtagata) and south-eastern (Palong-Zangbo) Tibetan Plateau were analysed in order to reveal the mineralogical and morphological characteristics of the analogue of long-range transported Asian dust. The results reveal that the dust particles are mainly composed of quartz (17-36%, number abundance), clay (37-48%) and feldspar (12-18%). Illite and chlorite are the dominant clay species, while kaolinite is rarely observed. For the three sites, regional differences in the mineral assemblages are significant, in particular the abundance of quartz, chlorite and muscovite species, reflecting the regional provenance of these dust particles and the climatic regime in their source areas. Oxide ratios in clays indicate different weathering strengths of the particles in their source regions, with a higher K2O/(SiO2 + Al2O3) in the western and northern Tibetan Plateau. The individual particles have modes of 1.48 and 1.53 in the aspect ratio and circularity distribution respectively. No significant relationship between aspect ratio and circularity was found. Quartz and feldspar particles have a narrow aspect ratio distribution. Muscovite particles have the coarsest grain size, while chlorite particles have the finest.